(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Objective: The aim of the study is to evaluate the effect of the Hydroalcoholic extract of Moringa oleifera leaves on fertility hormone and semen quality of male albino rats. Materials and method: The Hydroalcoholic extract of Moringa oleiferaseed at doses of 100, 200 and 400 mg/kg were administrated for 30 days. The effect of the extract on body weight and sexual organs weights (testes and epididymis) were determined. The fertility hormone and semen characteristic was studied. Resultsand and discussion: Oral administration of Hydro alcoholic extract at doses of 100, 200 and 400 mg/kg were significantly increased body weight and sexual organ weight. Also significantly increased serum Testosterone, Follicle-stimulating hormone (FSH) and Luteinizing hormone (LH) compared to the control group, in addition, significantly increased semen characteristic in experimental animals study. Conclusion :The results of the present study demonstrate the effectiveness of Moringa oleiferaseed extract on fertility hormones stimulator and improvement of semen characteristic which justify the traditional use of the plant as aphrodisiac and for management of male certain sexual disorders